COMPOSITION OF THE CATCH AND OPERATION OF SONDONG FISH FISHING GEAR IN THE WATERS OF RUPAT STRAIT, DUMAI, RIAU - Achmad, Asyarul; Rosana, Nurul; Sofijanto, Mochamad A (Politeknik Kelautan dan Perikanan Dumai, 2025)
This study aims to determine the type and composition of the catch, as well as describe the operation of the sondong fishing gear (push net) in the waters of the Rupat Strait, Dumai City, Riau Province. The method used is a descriptive method with quantitative and qualitative approaches. Data collection was carried out through direct observation, interviews with fishermen from KM Camar Laut, and documentation of catches from January to June 2025. The results of the study indicate that the sondong fishing gear has a simple construction with high effectiveness in catching white shrimp (Penaeus sp) as the main catch. In addition, there are bycatch in the form of senangin fish, gulama fish, sole fish, flatfish, black pomfret, swimming crab, sea eel, and tiger shrimp. The discarded catch that has no economic value is dominated by puffer fish (Tetraodon sp). Of the total catch of ±2,437 kg, approximately 43.4% is the main catch, 25.2% is bycatch, and 31.4% is discarded. Although effective, this tool is considered less selective and has the potential to damage the waters bottom. Therefore, sustainable management and monitoring of the use of sondong fishing gear is needed so as not to threaten the sustainability of the marine ecosystem in the area.